GENETIC ESTIMATES AND GENE ACTION FOR OBTAINING PROMISING HETEROTIC HYBRIDS IN BOTTLE GOURD [LAGENARIA SICERARIA (MOLINA) STANDL.] - P. K. RAY; G. C. YADAV; D. K. BARANWAL; H.K. SINGH (The Bioscan, 2015)
Gene action, magnitude of exploitable heterosis and combining ability variance and its effects were studied through half diallel analysis including 45 F1 hybrids derived by crossing ten diverse bottle gourd parents for earliness and yield components. Data was recorded for twelve quantitative traits including 5 maturity traits for earliness. Ratio of GCA and SCA variance revealed preponderance of non- additive genetic variance for all studied traits except fruit length. The genetic ratio H2/4H1 revealed that the asymmetrical distribution of the positive and negative alleles at all loci for most of the traits. All traits exhibit below 50 per cent narrow sense heritability except fruit length (72%). The average degree of dominance (H1/D)1/2 revealed that over dominance gene action for most of the yield related traits except fruit length. The best performing F1 hybrids regarding earliness, standard heterosis, SCA effects and mean performance of crosses were found in crosses Pusa Naveen x NDBG-603, NDBG-707-2 x NDBG-603 and NDBG-707-2 x NDBG-624. Based on earliness, desirable fruit shape and high fruit yield, elite hybrids were NDBG-707-2 x NDBG-624, NDBG-51 x NDBG-601 and NDBG-517 x NDBG-751.